THE USE OF CONJUNCTIONS IN STUDENTS’ WRITTEN NARRATIVE TEXTS: A CASE OF THE NINTH GRADE STUDENTS OF SMP PGRI 01 SEMARANG - Mazida, Lina (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
In writing narrative text, students must use conjunctions to make a coherence and a cohesion in the text. Most of students are lack of knowledge in using conjunction for writing narrative text. This study aimed to find out kind of conjunctions that students use in writing narrative texts, the conjunction errors found in it, and the teacher’s way in overcoming the errors. The research method was qualitative descriptive. The object of the research was students’ knowledge about the use of conjunctions in writing narrative texts in ninth grade SMP PGRI 1 Semarang in the 2022/2023 academic year. The data was gained through observation, and questionnaire. This research used Miles et al theory for the technique of analyzing the data, namely data condensation, data display, and drawing conclusions. This research found 161 coordinating conjunctions, and 96 subordinating conjunctions. There were two types of error conjunction in students’ narrative text writing namely omission and misuse. For overcoming conjunction error teacher gave feedback to the students’ works, it supported that the students also need to understand the use of conjunction. Teacher needs to giving motivation to the students, meanwhile the students have to analyze more when they write a narrative text.